2009
DOI: 10.1590/s0102-311x2009001200003
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural hearing loss in high school teenagers in Mexico City and its relationship with recreational noise

Abstract: The aim of this study was to measure the frequency of hearing loss in a sample of typical public high-school students exposed to recreational noise, and determine associated risk factors. The sample was made up of 214 teenagers from a high-school in Mexico City; subjects were selected randomly per strata. We applied a questionnaire to identify risk factors for hearing loss and performed a battery of audiologic tests consisting of otoscopy, tympanometry, and pure-tone audiometry. The mean age of the sample was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
1
15
0
5
Order By: Relevance
“…Rosanowski et al, [49] found no pure tone hearing loss but found transient effects on hearing and tinnitus immediately after exposure. Martinez-Wbaldo Mdel et al, [50] reported high-frequency hearing loss in 21% of the high-school students in Mexico, which was primarily related to frequent exposure to music at discotheques and pop-concerts, the use of personal devices and noise exposure in school workshops. A study in Brazil [51] among young adults confirmed these findings, indicating that a substantial percentage of the participants reported temporary tinnitus (69%) after attending discos and concerts and listening to music through headphones.…”
Section: Hearing Effectsmentioning
confidence: 99%
“…Rosanowski et al, [49] found no pure tone hearing loss but found transient effects on hearing and tinnitus immediately after exposure. Martinez-Wbaldo Mdel et al, [50] reported high-frequency hearing loss in 21% of the high-school students in Mexico, which was primarily related to frequent exposure to music at discotheques and pop-concerts, the use of personal devices and noise exposure in school workshops. A study in Brazil [51] among young adults confirmed these findings, indicating that a substantial percentage of the participants reported temporary tinnitus (69%) after attending discos and concerts and listening to music through headphones.…”
Section: Hearing Effectsmentioning
confidence: 99%
“…One cross-sectional study (n = 214, 14–19 years old) demonstrated a statistically significant association between concert attendance and hearing loss. 40 A small prospective cohort (n = 14) demonstrated significant high frequency hearing loss after repeated controlled exposures to live rock-and-roll music, but also noted that hearing thresholds had improved at the 5-month follow-up. 41 Another longitudinal study demonstrated significant hearing changes correlated with frequent discotheque attendance over a 12-week period.…”
Section: Impact Of Noise Exposure On Pediatric Hearing Lossmentioning
confidence: 99%
“…[9,10] Hearing loss among young people in different parts of the world is becoming increasingly common and a major public health concern. For example, among Mexican high school students hearing loss is significantly related to recreational activities such as club and concert visits, [11] as is also the case among Brazilian [9] and American students. [12] A study of 258 American adolescents indicated that 26% had thresholds poorer than the screening level of 20 dBHL.…”
Section: Introductionmentioning
confidence: 95%